Towards mission-based structural design for arctic regions. Issue 3 (2nd September 2017) - Ehlers, Soren; Cheng, Fai; Jordaan, Ian; Kuehnlein, Walter; Kujala, Pentti; Luo, Yu; Freeman, Ralph; Riska, Kaj; Sirkar, Jaideep; Oh, Yeong-Tae; Terai, Koji; Valkonen, Janne
ABSTRACT: Structures used in Arctic regions must comply with ice-induced loading without failure, asset loss, or loss of life. Current structural design regulations, particularly for ships, rely primarily on the experience gained from first-year ice, e.g. in the Baltic Sea. Therefore, this paper presents first, the most relevant design rules for both ships and offshore structures, and second, first principle-based pressure and occurrence determination methods to obtain corresponding scantlings. To demonstrate these first principle-based methods, the design ice load is assessed for a transit operation along the Northern Sea Route. In conclusion, this paper seeks to motivate a more mission-based design methodology, in addition to the present design methods, using the presented first principle-based methods. The paper is based on the ISSC 2015 V.6 Arctic Technology committee report.